A Series of Saddle - Node Bifurcation and Chaotic Behavior of a Family of a Semi - Triangular Maps - Salma Faris; Ammar Jameel (Al-Rafidain Journal of Computer Sciences and Mathematics)
This paper studies the bifurcations in dynamics of a family of semi-triangular maps . We will prove that this family has a series of Saddle-node bifurcations and a period doubling bifurcation. Also, we show that for some value of the parameter the functions  will be chaotic.